Antimicrobial potency, prevention ability, and killing efficacy of daptomycin-loaded versus vancomycin-loaded β-tricalcium phosphate/calcium sulfate for methicillin-resistant Staphylococcus aureus biofilms - Zhang, Xin; Chen, Peng; Wan, Hao-yang; Zhu, Run-jiu; Zhou, Yue; Song, Ming-rui; Jiang, Nan; Yu, Bin (Frontiers in Microbiology, 2022)
Growing evidence has shown that the efficacy of systemic administration of daptomycin for the treatment of methicillin-resistant Staphylococcus aureus (MRSA)-related infections is satisfactory. However, the clinical efficacy of the local administration of daptomycin for the management of osteoarticular infections remains unclear. This in vitro study compared the efficacy of daptomycin and vancomycin against MRSA biofilms. The elution kinetics of daptomycin and vancomycin, combined with gentamicin and loaded with either β-tricalcium phosphate/calcium sulfate or calcium sulfate, in the presence of MRSA infection, was assessed. Their efficacy in preventing biofilm formation and killing pre-formed biofilms was assessed using colony-forming unit count and confocal laser scanning microscopy. In addition, the efficacy of daptomycin, vancomycin, and gentamicin in prophylaxis and eradication of MRSA biofilms was also evaluated. Daptomycin + gentamicin and vancomycin + gentamicin displayed similar antimicrobial potency against MRSA, by either β-tricalcium phosphate/calcium sulfate or calcium sulfate. In the prevention assays, both daptomycin + gentamicin and vancomycin + gentamicin showed similar efficacy in preventing bacterial colony formation, with approximately 6 logs lower colony-forming units than those in the control group at both 1 and 3 days. The killing effect on pre-formed biofilms showed significant decreases of approximately 4 logs at 1 and 3 days following treatment with daptomycin + gentamicin and vancomycin + gentamicin. In addition, the confocal laser scanning microscopy results support the colony-forming unit data. Moreover, single use of vancomycin and gentamicin showed similar efficacies in preventing and killing MRSA biofilms, both of which were better than that of gentamicin. Our study demonstrated that vancomycin + gentamicin and daptomycin + gentamicin loaded with β-tricalcium phosphate/calcium sulfate or calcium sulfate showed similar prophylactic and killing effects on MRSA biofilms, implying a potential indication of local administration daptomycin for the treatment of MRSA-associated osteoarticular infections, especially if vancomycin administration presents limitations.